From fragility to recovery: a case of severe acute malnutrition in a 22-month-old - Aijaz, Ayesha; Bhupathi, Meghana; Sakinala, Eswar K.; Kondamadugula, Pavan S. R. (International Journal of Contemporary Pediatrics, 2025)
Severe acute malnutrition (SAM) remains a major public health concern in many low-income and middle-income countries. It is characterized by markedly low weight-for-height (less than –3 z-scores according to World Health Organization (WHO) growth standards), evident severe wasting, or nutritional edema. Affected children have an estimated 9–11-fold greater risk of illness and death than those with adequate nutrition. This case report highlights the clinical presentation, diagnostic challenges, and management of a 22-month-old female patient diagnosed with SAM. The child presented with inadequate growth, recurrent infections, and severe nutritional deficits compounded by delayed weaning and improper feeding practices. Examination revealed hallmark signs of malnutrition, including stunting, muscle wasting, and dermatosis. Laboratory findings indicated anemia and leukocytosis, which further supported the diagnosis. The management adhered to the WHO’s 10-step protocol for SAM, incorporating nutritional rehabilitation, micronutrient supplementation, and infection control, which led to gradual improvement. This case highlights the complex and varied causes of SAM, and stresses the need for timely management, improved community awareness regarding adequate nutrition, and coordinated care involving multiple health disciplines. Addressing the underlying causes of malnutrition is crucial for prevent recurrence and improve outcomes.